2004
DOI: 10.1007/s00259-004-1486-0
|View full text |Cite
|
Sign up to set email alerts
|

68Ga-labelled DOTA-derivatised peptide ligands

Abstract: 68Ge/68Ga generators provide cyclotron-independent access to positron emission tomography (PET) radiopharmaceuticals. We describe a system which allows the safe and efficient handling of 68Ge/68Ga generator eluates for labelling of DOTA-derivatised peptide ligands. The system comprises concentration and purification of the 68Ga eluate as well as labelling and purification steps for peptides, and can be used with different 68Ge/68Ga generator types. The suitability and efficiency were tested with two different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
141
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(152 citation statements)
references
References 4 publications
1
141
0
3
Order By: Relevance
“…While 68 Ge breakthrough generally met the manufacturer specifications, occasionally 68 Ge breakthrough values as high as 0.02% were observed. Better performance with regard to 68 Ge breakthrough has been reported by other investigators using this generator system (Meyer, et al, 2004). As with all radiopharmaceuticals derived from generator-produced radionuclides and intended for human use, careful monitoring of parent breakthrough is clearly necessary for accurate estimation (and control) of patient radiation exposure, especially when the product involves a relatively long-lived parent.…”
Section: Resultsmentioning
confidence: 72%
“…While 68 Ge breakthrough generally met the manufacturer specifications, occasionally 68 Ge breakthrough values as high as 0.02% were observed. Better performance with regard to 68 Ge breakthrough has been reported by other investigators using this generator system (Meyer, et al, 2004). As with all radiopharmaceuticals derived from generator-produced radionuclides and intended for human use, careful monitoring of parent breakthrough is clearly necessary for accurate estimation (and control) of patient radiation exposure, especially when the product involves a relatively long-lived parent.…”
Section: Resultsmentioning
confidence: 72%
“…Interestingly, the authors also tested cationic exchange purification (SCX) method, with no particular difference compared to the SAX based method. The fractionated elution method yielded a very high 68 Ga-activity, but it has been reported that SCX/SAX postprocessing is more efficient than fractionated elution of the generator [44][45][46][47][48], mainly reducing co-eluted metal impurities and 68 Ge-breakthrough levels. We focused on the impact that a simple post-processing procedure has on the crude %LE of the NOTA-peptide conjugates.…”
Section: G a C O M P L E X A T I O N W I T H P E P T I D E S F U N C mentioning
confidence: 99%
“…Recently, there has been renewed interest in the use of 68 Ga for PET imaging [10][11][12][13]. Of particular interest is the recent development of 68 Ga-labeled peptides targeting endocrine tumor receptors [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%